HMGA proteins regulate the expression of FGF2 in uterine fibroids - Helmke, Burkhard Maria; Markowski, Dominique Nadine; Müller, Marietta Henrike; Sommer, Anette; Müller, Jörg; Möller, Carsten; Bullerdiek, Jörn (Molecular human reproduction, 2011)
In human fibroids genes encoding the high-mobility proteins containing the ‘AT-hook’ DNA-binding motif (HMGA) are frequently affected by non-random chromosomal rearrangements. Thus, the different proteins and their derivatives resulting from these genomic rearrangements can be assumed to be involved in the genesis of these tumors by activation of largely identical downstream pathways. Constructs encoding HMGA proteins and their relevant derivatives were overexpressed in human myometrial cells, and RNA isolated from these cells was hybridized to filter arrays. Four genes were either up- or down-regulated at least 2-fold after overexpression of either of the HMGA genes and their derivatives. FGF2 (fibroblast growth factor 2) was one of these genes, and we were then able to show by microarray analyses that tumors with rearrangements of the HMGA2 locus (n = 8) expressed significantly higher levels of FGF2 than those with an apparently normal karyotype (n = 47). Accordingly, by quantitative real-time PCR uterine leiomyomas with rearrangements of the HMGA2 locus were found to express significantly higher levels of FGF2 than those with an apparently normal karyotype with a linear relationship between the expression of FGF2 and the level of HMGA2 overexpression as well as the tumor size. The results of western blot analyses confirmed these findings. Moreover, stimulation of myometrial tissue by FGF1, a strong inducer of HMGA2, leads to an increase of HMGA2 as well as FGF2 expression. In conclusion, the results contribute to the understanding of the association between the overexpression of HMGA proteins, the regulation of FGF2 expression and the size of fibroids.